Analysis of Inflation Trends in Urban and Rural Parts of Azerbaijan: Main Drivers and Links to Oil Revenue - Ibrahim Niftiyev (SSRN, 2020)
Inflation is one of the most important economic indicators for a country. Understanding inflation based on the consumer spending patterns allows for better conceptualization of the phenomenon and improved policy responses for the unwanted developments, more precisely, increased price levels in consumer markets. The current working paper develops Consumer Price Index-based inflation indicator via the help of the Laspeyres price index in the case of Azerbaijan to evaluate the post-booming period (which is since 2011). Moreover, the significant results of correlation analysis between the Paasche Price Index and oil prices, oil revenue, and real effective exchange rate (REER) demonstrate initial signals about the urban and rural inflation dynamics and trends in the case of oil-rich Azerbaijan.
Keywords: E01; E31; F41; O50; 330; Inflation; Macroeconomic Data; Consumer Price Index (CPI); Oil revenue; Laspeyres Index; Paasche Index; Azerbaijan Economy